Utilizing Marketing Technology and Product Innovation as Infrastructure for the Development of East Sawarna Village Banana Sale MSMEs - Deris Desmawan; Rizal Syaifudin; Ewing Yuvisa Ibrani Ibrani (EQUATOR SINAR AKADEMIA, 2026)
Bananas are an agricultural commodity with high economic value and broad market demand. They serve as both a staple food and a source of income for many farmers and entrepreneurs. However, in the face of increasing competition, the banana industry often encounters challenges in enhancing sales and expanding its market reach. This community service program is designed to utilize marketing technology as an effective solution for MSMEs to address these challenges. By implementing digital marketing strategies, such as the use of social media, this initiative supports the national agenda of economic digitalization and aligns with the mandate of higher education to generate measurable social impact through community service.